A new prenylated hydroquinone from the roots of Garcinia atroviridis Griff ex T. Anders (Guttiferae) - Permana, Dharma; Lajis, Nordin; Shaari, Khozirah; Ali, Abdul M.; Mackeen, Mukram M.; Kitajima, Mariko; Takayama, Hiromitsu; Aimi, Norio (De Gruyter, 2003)
A continuing study on the phytochemical constituents of Garcinia atroviridis Griff ex T. Anders (Guttiferae) has led to the isolation of a new prenylated hydroquinone from the roots of the plant. The compound has been elucidated to be 4-methylhydroatrovirinone, primarily by the use of gradient NMR and mass spectroscopy. The roots also yielded the known morelloflavone and its 7-O-β-D-glucopyranoside, fukugiside, together with 14-cis-do-cosenoic acid.